Children Born out of Wedlock Inherit the Lineage of Their Biological Father: Auda's Maqāşid asy-Syarī'a Perspective - Al-Mabruri, M. Nasikhul Umam; Rizki, Wahyu Fahrul; Hakimi, Abdul Rahim (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: This article discusses the debate of the lineage (nasab) of children born out of wedlock according to maqāşid asy-syarī'a framework by Auda. The data were collected from various literary sources, including primary, secondary, and tertiary materials. By employing the approach and theory of maqāşid asy-syarī'a of Auda, this article concludes that efforts to create a just and equitable jurisprudence can be undertaken by reconstructing the classical fiqh framework concerning the status and rights of children born out of wedlock. This article also concludes that every child fundamentally possesses the same legal status and civil rights, including the right to lineage with their biological father. This is made possible by establishing the reconstruction of the lineage of children born out of wedlock on a substantive-legal basis rather than a formal-legal basis, as found in the classical fiqh construction.Abstrak: Artikel ini mendiskusikan perdebatan mengenai nasab anak yang lahir di luar pernikahan menurut kerangka maqāşid asy-syarī'a ala Auda. Data dikumpulkan dari berbagai sumber pustaka, termasuk bahan primer, sekunder, dan tersier. Dengan menerapkan pendekatan dan teori maqāşid asy-syarī'a karya Auda, artikel ini menyimpulkan bahwa upaya untuk menciptakan yurisprudensi yang adil dan merata dapat dilakukan dengan merekonstruksi kerangka fikih klasik mengenai status dan hak-hak anak yang lahir di luar pernikahan. Artikel ini juga menyimpulkan bahwa setiap anak pada dasarnya memiliki status hukum dan hak-hak sipil yang sama, termasuk hak atas nasab dengan ayah biologis mereka. Hal ini dapat tercapai dengan melakukan rekonstruksi nasab anak yang lahir di luar pernikahan berdasarkan dasar hukum substantif daripada dasar hukum formal, seperti yang ditemukan dalam konstruksi fikih klasik.